NGHIÊN CỨU KHẢ NĂNG THÍCH ỨNG VỚI ĐIỀU KIỆN ÁNH SÁNG CỦA LOÀI SÂM LÔNG (Cyclea barbata Miers) TRỒNG THỬ NGHIỆM TỪ HẠT VÀ RỄ TẠI VƯỜN QUỐC GIA CÁT TIÊN - Nguyễn, Thị Vân (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE STUDY OF THE ADAPTATION OF Cyclea barbata Miers TO NATURAL LIGHTING CONDITIONS IN FIELD TRIALS OF SEEDS AND ROOTS IN CAT TIEN NATIONAL PARKThe study is conducted to survey the influences of 100% and 60% natural lighting on Cyclea barbata Miers in field trials of seeds and roots. The physiological parameters such as LAR, SLA, NAR as well as relative growth rate RGR found in the two conditions of lighting are not significantly different, which shows that the Cyclea barbata has a wide range of lighting condition and the mature plants can acclimate to a high lighting condition. Moreover, Cyclea barbata Miers growing up under the forest canopy in Nam Cat Tien is supposed to belong to the truderal plant at top R of CRS triangle and the plants of roots grow better than the plants of seeds.